2020
DOI: 10.1098/rspb.2020.1459
|View full text |Cite
|
Sign up to set email alerts
|

Angels in disguise: sympatric hybridization in the marine angelfishes is widespread and occurs between deeply divergent lineages

Abstract: Hybridization events are not uncommon in marine environments where physical barriers are attenuated. Studies of coral reef taxa have suggested that hybridization predominantly occurs between parapatric species distributed along biogeographic suture zones. By contrast, little is known about the extent of sympatric hybridization on coral reefs, despite the large amount of biogeographic overlap shared by many coral reef species. Here, we investigate if the propensity for hybridization along suture zones represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Parallel hybrid phenomena may occur in the angelfishes (Pomacanthidae). A recent survey of hybridization within the Pomacanthidae found that 59% of 37 hybridizing species pairs had sympatric distributions (defined by 50% range overlap) and some species pairs had older divergence dates as indicated by mtCO1 divergence between 5 and 8% [ 24 ]. Intriguingly, protogynous hermaphroditism is common in both the parrotfishes and the angelfishes, with mating system attributes that may facilitate heterospecific mating, as described under The breakdown of pre-mating isolation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parallel hybrid phenomena may occur in the angelfishes (Pomacanthidae). A recent survey of hybridization within the Pomacanthidae found that 59% of 37 hybridizing species pairs had sympatric distributions (defined by 50% range overlap) and some species pairs had older divergence dates as indicated by mtCO1 divergence between 5 and 8% [ 24 ]. Intriguingly, protogynous hermaphroditism is common in both the parrotfishes and the angelfishes, with mating system attributes that may facilitate heterospecific mating, as described under The breakdown of pre-mating isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, protogynous hermaphroditism is common in both the parrotfishes and the angelfishes, with mating system attributes that may facilitate heterospecific mating, as described under The breakdown of pre-mating isolation. On the other hand, in 85% (n = 20) of angelfish hybrid zones where observations of abundance were available, one or both parental species were rare [ 24 ], an ecological pattern that clearly does not apply to the Scarus hybrid complex in the TEP where all three parental species are conspicuously abundant (Fig. 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison Randler (2006) found that hybridization was more frequent between parapatric than sympatric species, although Randler notes that there are exceptions to this pattern and similar to Willis et al (2014) states that sympatry may increase the potential for individuals to find mates (Tubaro and Lijtmaer 2002). Across taxa there is growing evidence that hybridization is common in natural populations among deeply divergent lineages and that sympatry may help to facilitate these events (Jasso-Martínez et al 2018, Tea et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization is common in natural populations. Although it was previously thought that hybridization occurred exclusively between closely related species (Dasmahapatra et al 2007), it is now recognized that hybridization occurs between deeply divergent lineages (Jasso‐Martínez et al 2018, Joseph et al 2019, Tea et al 2020). Questions remain about the processes that facilitate the events; for example does hybridization occur because species live in sympatry or does hybridization occur because species exhibit ecological or habitat similarities (Willis et al 2014, Wood et al 2016, Kyogoku and Kokko 2019)?…”
Section: Introductionmentioning
confidence: 99%